An empirical broad spectrum antibiotic therapy in health‐care–associated infections improves survival in patients with cirrhosis: A randomized trial. Issue 5 (5th January 2016) - Merli, Manuela; Lucidi, Cristina; Di Gregorio, Vincenza; Lattanzi, Barbara; Giannelli, Valerio; Giusto, Michela; Farcomeni, Alessio; Ceccarelli, Giancarlo; Falcone, Marco; Riggio, Oliviero; Venditti, Mario
Abstract : Early diagnosis and appropriate treatment of infections in cirrhosis are crucial because of their high morbidity and mortality. Multidrug‐resistant (MDR) infections are on the increase in health care settings. Health‐care–associated (HCA) infections are still frequently treated as community‐acquired with a detrimental effect on survival. We aimed to prospectively evaluate in a randomized trial the effectiveness of a broad spectrum antibiotic treatment in patients with cirrhosis with HCA infections. Consecutive patients with cirrhosis hospitalized with HCA infections were enrolled. After culture sampling, patients were promptly randomized to receive a standard or a broad spectrum antibiotic treatment (NCT01820026). The primary endpoint was in‐hospital mortality. Efficacy, side effects, and the length of hospitalization were considered. Treatment failure was followed by a change in antibiotic therapy. Ninety‐six patients were randomized and 94 were included. The two groups were similar for demographic, clinical, and microbiological characteristics. The prevalence of MDR pathogens was 40% in the standard versus 46% in the broad spectrum group. In‐hospital mortality showed a substantial reduction in the broad spectrum versus standard group (6% vs. 25%; P  = 0.01). In a post‐hoc analysis, reduction of mortality was more evident in patients with sepsis. The broad spectrum showed a lower rate of treatment failure than the standard therapy (18% vs. 51%; P  = 0.001). Length of hospitalization was shorter in the broad spectrum (12.3 ± 7 days) versus standard group (18 ± 15 days; P  = 0.03). Five patients in each group developed a second infection during hospitalization with a similar prevalence of MDR (50% broad spectrum vs. 60% standard). Conclusions : A broad spectrum antibiotic therapy as empirical treatment in HCA infections improves survival in cirrhosis. This treatment was significantly effective, safe, and cost saving. (Hepatology 2016;63:1632‐1639)